2021
DOI: 10.3390/vaccines9111300
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-Staphylococcus aureus Single-Chain Fragment Variables Play a Protective Anti-Inflammatory Role In Vitro and In Vivo

Abstract: Staphylococcus aureus is a causative agent of bovine mastitis, capable of causing significant economic losses to the dairy industry worldwide. This study focuses on obtaining single-chain fragment variables (scFvs) against the virulence factors of S. aureus and evaluates the protective effect of scFvs on bovine mammary epithelial (MAC-T) cells and mice mammary gland tissues infected by S. aureus. After five rounds of bio-panning, four scFvs targeting four virulence factors of S. aureus were obtained. The compl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(10 citation statements)
references
References 63 publications
3
7
0
Order By: Relevance
“…At present, there is no efficient treatment for bovine mastitis. Previous studies in our lab have shown that scFvs targeting different antigens had a significant protective effect on mastitis in mice [ 8 , 25 , 40 ]. In brief, we obtained four scFvs (ZL8 and ZL42 aimed at LukE, ZL22 and ZL23 aimed at LukD) using the phage display technique.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…At present, there is no efficient treatment for bovine mastitis. Previous studies in our lab have shown that scFvs targeting different antigens had a significant protective effect on mastitis in mice [ 8 , 25 , 40 ]. In brief, we obtained four scFvs (ZL8 and ZL42 aimed at LukE, ZL22 and ZL23 aimed at LukD) using the phage display technique.…”
Section: Discussionmentioning
confidence: 99%
“…Staphylococcus aureus ( S. aureus ) is a major opportunistic pathogen of humans and animals and one of the most pathogenic microorganisms in bovine mastitis [ 5 , 6 , 7 ]. S. aureus can secrete large amounts of virulence factors, such as fibronectin-binding protein A (FnBPA), coagulase (Coa), β-hemolysin (Hlb), glyceraldehyde-3-phosphate dehydrogenase (GapC) and leukotoxin [ 8 , 9 , 10 ]. The interaction between virulence factors is the main reason for the pathogenicity of S. aureus [ 1 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations